BEZPIECZEŃSTWO WSCHODNIEJ FLANKI NATO W KONTEKŚCIE ZAGROŻEŃ MILITARNYCH KREOWANYCH PRZEZ FEDERACJĘ ROSYJSKĄ - MISZCZUK Marcin (2024)
The aim of this article is to explain contemporary threats to the security of the NATO’s Eastern Flank and to forecast future activities of the North Atlantic Treaty Organization in relation to new threats created by the Russian Federation. A research problem in the article is contained in the form of a question: Which threats will be present in the security space of NATO’s Eastern Flank within a decade and which actions need to be implemented by the Alliance to optimise its defence capabilities? During the research process, it was established that the Russian Federation has the abilities to conduct international competition using military means and non-kinetic forms of influence. The following main hypothesis was assumed: It is presumed that military threats and destabilising forms and methods of aggression below the level of open armed conflict will be present in the security space of NATO’s Eastern Flank within a decade. The emerging threats and challenges to the Alliance’s security will at the same time be the reason for the process of optimising the capacity of the Allied armed forces for effective defence and deterrence, as well as a catalyst for the process of regional integration activities in the defence context, in a multilateral or bilateral format, implemented at the political level. It is believed that countries located on NATO’s Eastern Flank may be most exposed to threats generated by the Russian Federation over the next decade due to geographical location, historical conditions and the foreign policy goals of the Russian Federation. The analysis of the Russian Federation’s operations in Ukraine and the achievements of the Russian Armed Forces in Syria and Georgia prove the need for the North Atlantic Treaty Organization to take optimization actions in order to counteract the threats that may result from the revisionist international policy of the Russian Federation in the strategic perimeter of Central and Eastern Europe. It is believed that future NATO adaptation activities may be related to increasing defence spending of member states, intensifying the process of acquiring equipment and weapons and developing the capabilities of NATO’s Armed Forces in the field of nuclear deterrence and the use of precision weapons. The research methods used in the study are critical analysis and evaluation of the literature, analysis, the method of threat development forecast and synthesis.